Wheel-Set Hunting Movement and its Contribution to Coupling Vibration of Vehicle-Bridge System. Issue 1 (January 2013) - Cheng, Q.; Zhang, N.; Xia, H.; Zhang, T.; Du, X.T.
Wheel-set hunting is an important and random lateral movement when wheel-set running on the track. Firstly a vehicle-bridge dynamic interaction model is established, in which the lateral wheel-rail interaction is defined by Kalker linear creep theory with the calculation of detailed wheel-rail contact adhesion geometric parameters and creep force. Then with the case of a high speed train passing a 32 m simply-supported beam bridge, the wheel-set hunting movement is calculated according to the relative vehicle and bridge lateral movement. And the characteristics of wheel-set hunting with different train speed and bridge stiffness are discussed. Then a simple lateral wheel-rail interaction is defined with close contact and no elastic deformation, and the contribution of hunting movement to coupling vibration of vehicle-bridge system is summarized in this method. The results show that the wheel-set hunting movement could be neglected when analyzing the bridge response, but it should be considered when analyzing the vehicle response in the vehicle-bridge interaction.